Introduction Trials on Grevillea pterldifolia (Syn. G. Banksil) Germination Behaviour of Seeds at Nursery Stage under Dehradun Climatic Conditions - Bahuguna, V. K.; Lal, Pyare (Indian Forester, 1994)
The paper presents the results of an investigation carried out at the Plant Introduction Nursery of Silviculture Division of FRI, Debradun with a view to finding the best combination of soil mixture, method of sowing and best containers for getting healthy and vigorously growing plantable seedlings of Grivelleapteridifolia. The results of this experiment indicated that the seeds of this species may be sown in nursery beds (line sowing) or polythene bags by filling the soil mixture of soil and sand in 2:1 or 1:1 ratio for better results.